Apixaban vs. Warfarin in Atrial Fibrillation Patients With Chronic Kidney Disease - Fu, Chung-Ming; Li, Lung-Chih; Lee, Yueh-Ting; Wang, Shih-Wei; Hsu, Chien-Ning (Frontiers in Cardiovascular Medicine, 2021)
Background and objectives: Real-world evidence of apixaban treatment in patients with chronic kidney disease remains scarce. This study aimed to compare the relative risk of stroke or systemic embolism (SE) and major bleeding between apixaban and warfarin in atrial fibrillation (AF) patients with different degrees of kidney function. Design, setting, participants, and measurements: We evaluated newly diagnosed AF patients between 2004 and 2018, who were receiving apixaban or warfarin. Electronic medical record data were collected from a large healthcare delivery network in Taiwan. The outcomes of hospitalization for stroke/SE and major bleeding were compared with propensity-score matched apixaban and warfarin cohorts. Stratified analyses according to initial apixaban dose (standard dose of 10 mg/day versus lower dose of 2.5–5.0 mg/day) and baseline estimated glomerular filtration rate were performed. Results: Each cohort involved 1625 matched patients. Apixaban was significantly associated with a lower risk of stroke/SE (adjusted hazard ratio [aHR]: 0.74; 95% confidence interval [CI]:0.57–0.97; p=0.03). The risk of major bleeding was not increased whether in standard doses (aHR: 0.66; 95% CI: 0.45–0.96; p=0.03) or reduced doses (aHR, 0.84; 95% CI, 0.63–1.12; p=0.23) of apixaban. Regarding kidney function, apixaban reduced the risk of stroke/SE by 37% in those with an eGFR of <30 ml/min/1.73 m2 (aHR: 0.63; 95% CI: 0.40–0.98; p=0.04). Conclusions: Compared to warfarin, apixaban is associated with a reduced risk of stroke/SE and is consistent with a subset of AF patients with eGFR <30 ml/min/1.73 m2. Both standard and reduced doses of apixaban showed lower risk of major bleeding than those of warfarin.